THE CRYSTAL STRUCTURE OF ANTHROPOGENIC PB2(OH)3(NO3), AND A REVIEW OF PB-(O,OH) CLUSTERS AND LEAD NITRATES - Kolitsch U.; Tillmanns E. (My University, 2003)
The previously unknown crystal structure of the basic lead nitrate Pb2(OH)3(NO3) has been determined using single-crystal X-ray diffraction data (Mo-Kα radiation, CCD area detector). The compound is orthorhombic, space group Immm, with a = 8.314(2), b = 8.545(2), c = 17.210(3) Å(R 1 = 2.78% for 940 'observed' reflections with Fo > 4(Fo)). The layered structure contains a previously unknown cuboid [Pb8(OH)12]4+ cluster and NO3 groups. The study used crystals formed by anthropogenic processes on a medieval mine dump, probably involving black gunpowder used in the blasting of ore. Pb2(OH)3(NO3) is associated with a second nitrate, Pb13O8(OH)6(NO3)4, which was previously designated as "Pb6O3(OH)4(NO3)2" or "Pb3(OH)5(NO3)". It is rhombohedral, space group R3, with a = 10.263(1), c = 25.454(5) Å, and a structure solution is in complete agreement with an independent single-crystal study by Li et al. (2001). Probable hydrogen bonds in Pb2(OH)3(NO3) are indicated. Reported data on [Pbx2+(O,OH)y]n+ clusters and lead hydroxide and oxide nitrates are summarized and discussed critically. The probable conditions of formation of the studied samples are evaluated.